Les formations universitaires en urbanisme en France : un nouveau gouvernement des corps (de métiers) - Guillaume Faburel (Unité Mixte de Recherche 8504 Géographie-cités, 2017)
More than any other discipline, urbanism interacts with the world which it makes intelligible by its knowledge, and apprehendable by its courses. However, the issues that govern urban developments have changed in nature and scope. We show how teachings in urban planning, mainly in master’s degree, have moved away from analytical perspectives and critical orientations, which are today more important than ever. Over the last thirty years, these trainings courses have experienced a real twist, which the competitive climate for the recognition of diplomas cannot explain. To date they comprise a specialized technical field, between profession repositories and standardization of careers, between the federation of Instituts d’urbanisme and the standardization of knowledge by the Comité National des Universités (CNU). The articulation between pluridisciplinarity and practical knowledge, structured in the 1970s and 1980s around noticed thoughts, has generally substituted another couple, both as a position and a process of formation: the action of hyper-urbanism (based on manufacturing processes and their management), technical know-how and their orientation towards economic development (based on projects and their instruments). By this twist, the current of urban studies has developed very little in France (although very widely deployed abroad). Furthermore, urban planning courses remain affected by a broad socio-ecological misconception.